Grassroots Security: The Meira Paibi Movement and the Intersection of Gender, Ethnicity, and Conflict in Manipur - Chaisingkananont, Somrak; Saisin, Atchareeya (Journal of Ethnic and Cultural Studies, 2026)
This article explores the Meira Paibi movement in Manipur, India, as a vital site of grassroots women’s activism operating within a militarized and ethnically contested landscape. Drawing on feminist security studies, intersectionality, and securitization theory, it examines how Meitei women redefine security through everyday acts of resistance, moral regulation, and community care. Originating in the late 1970s, the Meira Paibi or “women torchbearers” have evolved into informal agents of justice, patrolling streets, confronting state violence, and upholding social norms. Using a documentary-based methodology, this study analyzes how the Meira Paibi challenge dominant security discourses and engage in counter-securitizing acts, exemplified by the 2004 naked protest custodial violence. Their activism blurs boundaries between public and private, and resistance and regulation, exposing the embodied and relational dimensions of grassroots security. Yet the movement is not without contradictions: while confronting militarized patriarchy and challenging the state, their exercise of moral authority often reinforces maternalistic authority, moral conservatism, and community-level biopolitical regulation. By situating Meira Paibi within critical feminist and security frameworks, the article contributes to broader debates on gendered resistance, informal governance, and localized peacebuilding, arguing that women’s agency in conflict zones must be understood through a nuanced lens that embraces both their emancipatory potential and their internal tensions.